2005
DOI: 10.1128/jvi.79.10.6023-6034.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Facilitates Hepatitis C Virus Infection, and Neutralizing Responses Inversely Correlate with Viral Replication Kinetics at the Acute Phase of Hepatitis C Virus Infection

Abstract: The factors leading to spontaneous clearance of hepatitis C virus (HCV) or to viral persistence are elusive. Understanding virus-host interactions that enable acute HCV clearance is key to the development of more effective therapeutic and prophylactic strategies. Here, using a sensitive neutralization assay based on infectious HCV pseudoparticles (HCVpp), we have studied the kinetics of humoral responses in a cohort of acute-phase patients infected during a single nosocomial outbreak in a hemodialysis center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
202
1
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(217 citation statements)
references
References 64 publications
7
202
1
7
Order By: Relevance
“…In addition, the role of virus-specific antibodies needs to be further addressed. In humans, HCV strain-specific neutralizing antibodies have been found to be associated with spontaneous recovery (43,44). Our reinfected horses displayed a higher titer of NPHV-specific antibodies before rechallenge, which even further increased after a new exposure.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, the role of virus-specific antibodies needs to be further addressed. In humans, HCV strain-specific neutralizing antibodies have been found to be associated with spontaneous recovery (43,44). Our reinfected horses displayed a higher titer of NPHV-specific antibodies before rechallenge, which even further increased after a new exposure.…”
Section: Discussionmentioning
confidence: 61%
“…39,40 SR-BI was initially reported as a candidate receptor for HCV because of its ability to bind to sE2. 14 Subsequent reports have shown that antibodies and siRNA targeting SR-BI inhibit HCVpp entry 15,17,41 (Fig. 4).…”
Section: Discussionmentioning
confidence: 94%
“…This finding raises the possibility that specific proteins released by human or chimpanzee hepatocytes enhance infectivity of HCV. This phenomenon has recently been observed in the HCV pseudovirus system, in which the entry of retroviral pseudovirus particles bearing the envelope proteins of HCV was found to be enhanced by serum from chimpanzees and humans, human lipoproteins, and human apolipoproteins (20)(21)(22)(23). Thus, it is a possibility that such lipoproteins and apolipoproteins might also enhance the infectivity of HCV in cell culture.…”
mentioning
confidence: 65%